2017
DOI: 10.1130/ges01525.1
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircons and sediment dispersal in the Appalachian foreland

Abstract: Seven new detrital-zircon U-Pb age analyses along with a compilation of previously published data from Mississippian-Permian sandstones in the Appalachian foreland (total n = 3564) define the provenance of Alleghanian synorogenic clastic wedges, as well as characterize the detritus available to any more extensive intracontinental dispersal systems. The samples are from the cratonward-prograding Mauch Chunk-Pottsville clastic wedge centered on the Pennsylvania salient, the cratonward-prograding Pennington-Lee c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 83 publications
11
97
0
Order By: Relevance
“…The strong Grenville and Acadian‐Taconic age peaks observed in the zircon age spectra for the Chesterian IVF sandstones point to more distant or potentially recycled sources for sediments. Both the Grenville and Taconic‐Acadian orogenies occurred in the Appalachian region, and comparison of our data with data from the Alleghanian Appalachian Foreland Basin, a proxy for sediment sources and likely zircon age distributions derived from the orogen, shows a high degree of similarity (Thomas et al, and references therein). The almost mirror image in age spectra between sandstones from the Hugoton Embayment and Appalachian signature derived from synorogenic clastic wedge sediments (Thomas et al, ), shown in Figure c, strongly suggests that the Appalachian region was the primary source of sediments.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…The strong Grenville and Acadian‐Taconic age peaks observed in the zircon age spectra for the Chesterian IVF sandstones point to more distant or potentially recycled sources for sediments. Both the Grenville and Taconic‐Acadian orogenies occurred in the Appalachian region, and comparison of our data with data from the Alleghanian Appalachian Foreland Basin, a proxy for sediment sources and likely zircon age distributions derived from the orogen, shows a high degree of similarity (Thomas et al, and references therein). The almost mirror image in age spectra between sandstones from the Hugoton Embayment and Appalachian signature derived from synorogenic clastic wedge sediments (Thomas et al, ), shown in Figure c, strongly suggests that the Appalachian region was the primary source of sediments.…”
Section: Discussionsupporting
confidence: 56%
“…Both the Grenville and Taconic‐Acadian orogenies occurred in the Appalachian region, and comparison of our data with data from the Alleghanian Appalachian Foreland Basin, a proxy for sediment sources and likely zircon age distributions derived from the orogen, shows a high degree of similarity (Thomas et al, and references therein). The almost mirror image in age spectra between sandstones from the Hugoton Embayment and Appalachian signature derived from synorogenic clastic wedge sediments (Thomas et al, ), shown in Figure c, strongly suggests that the Appalachian region was the primary source of sediments. However, it is worth noting that the percentages of Yavapai‐Mazatzal grains (1,800–1,600 Ma; up to 10%) in some samples are higher than in Appalachian sources and may point to some limited contributions from local basement uplifts such as Nemaha Uplift (Xie, O'Connor, et al, ).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations